Att lära i och för arbetslivet: Myter och utmaningar - Gustafsson, Jan; Rystedt, Hans (Pedagogisk forskning i Sverige, 2013)
Gustafsson, Jan & Rystedt Hans: Learing in and for working life: Myths and challenges. Pedagogisk Forskning i Sverige, Vol. 14, No. 2, pp. 110-133. Self-directed learning, autonomy and problem-solving have increasingly been put forward in education to foster competencies needed for modern working life. Needs for authenticity and pedagogical models like work based and problem based learning have emerged as responses to this requests. The implementation of a nursing programme building on such assumptions is analysed in this study by investigating how it is construed and managed by teachers and students themselves. The results showed that new tensions emerged between understanding problems on a theoretical level and how to construe and deal with clinical problems. It is concluded that the movement towards authenticity should further take in consideration how students actually construe and understand relations between content knowledge and real life problems in work based and problem-based learning environments. Keywords: Authenticity, nurse education, problem-based learning, work-based learning, work-integrated learning